The leadership and management styles and behaviors of subject coordinatiors in a sample of Lebanese secondary schools - Wazen, Cesar Elias (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2007)
Research on the role of the subject coordinators in secondary schools has shown that this role can influence the successful implementation of the school's visio n which in turn can influence teachers' performance and students' results. The f act that subject coordinators are the link between the administrators and the te achers makes them essential players in implementing this vision in the classroom . The importance given to this role varies among schools: from marginal in some schools to nearly 'venerated' in others. This study aims to investigate 1) the Bolman and Deal leadership and management styles of subject coordinators as perceived by coordinators and principals; 2) a ny differences in these perceptions of styles according to subject of instructio n, sector and gender; 3) the Bolman and Deal leadership and management behaviors of subject coordinators as perceived by coordinators and principals. The sample for this study is 16 coordinators randomly selected from public and p rivate schools in the Greater Beirut and Mount Lebanon area. Coordinators partic ipating in the study filled out a questionnaire adapted for this study. In addit ion, a sample of the 16 coordinators was interviewed regarding issues identified in the questionnaire. Finally, the eight heads of the schools to which the coordinators belong filled a similar version of the questionnaire and were interviewed to identify their pe rceptions of what the coordinators are doing. Data was analyzed to produce a pro file for each coordinator. These profiles were compared and contrasted to identi fy patterns among schools. Major findings of this study included the following: (1) The leadership and management styles of coordinators in Lebanese secondary s chools are Human Resources and Structural (2) Math and Male coordinators view th e structural style ranking first. Language and Female coordinators view the huma n resources style as ranking first. As for the principals, the Private and Femal e coordinators have a human resources dominant style. Public and Male coordinato rs have structural dominant style. (3) The behaviors determining the role of coo rdinators in Lebanese Secondary schools are: (1) Supportive, (2) Participative, (3) Analytic, and (4) Organized according to the perceptions of coordinators and their principals'.
: Mémoire
Keywords: Administration Scolaire; Cycle Secondaire; Educational administration; Leadership; Leadership; Secondary Education